(untitled) (International Journal of Medical and Surgical Sciences, 2017)
Regeneration is defined as the reproduction or reconstruction of a lost part or injury of the body in such a way that the architecture and function of the lost or injured tissue are completely restored. The goal of regenerative periodontal therapy is to restore the structure and function of the periodontium. The positive effects of Platelet-rich plasma (PRP) are attributed to the angiogenic, mitogenic and proliferative capacities of growth factors such as platelet-derived growth factor, transforming growth factor and vascular endothelial growth factor. Platelet-rich fibrin (PRF) is a second generation platelet concentrate that allows fibrin membranes enriched with platelets and growth factors to be obtained after starting an anticoagulant-free blood collection without any biomechanical artificial modification. The objective of this review is to know the efficacy of platelet-rich plasma and platelet-rich fibrin in the periodontal regeneration of intrabony defects. The clinical implications for this autologous material are promising. Further long term, larger, multicentred randomized controlled clinical trials are required to determine the effects of PRP and PRF on the regeneration of alveolar bone due to periodontal disease.